PERANCANGAN GAME PETUALANGAN SEBAGAI SARANA PEMBELAJARAN EDUKASI BERBASIS ANDROID - Anna; Riski Annisa; Robi Parwandar (LPPM STMIK STIKOM Indonesia, 2020)
Today, mobile devices are very popular with the public and the android operating system become the most famous mobile phone in the world because of its sophistication and efficiency to be everywhere. One feature that is often used in Android is a game. Learning by the method of reading through a book directly usually causes boredom for a reader while studying. Because of the identical content of the book, it usually contains only ordinary writing and pictures, so that a reader tends to get bored and lazy to learn more. Therefore, the author makes an adventure game that combines games and education, as a medium for learning and playing that is interesting. Game level consists of three levels where each level is given questions about accounting learning with different levels of difficulty. Making this game application is intended for Vocational High School students majoring in Accounting as well as for the general public to increase knowledge about accounting. This game was created using the Construct2 application based on HTML5 and Adobe Photoshop. Based on the results of research and submission of the questionnaire that the author did, it was found that the percentage of answers to the questions of 10 respondents stated that this game can increase knowledge about accounting, and overcome boredom in learning accounting.